LIVED EXPERIENCE OF PADLET AND MENTIMETER AS STUDENT RESPONSE SYSTEM (SRS) IN THE CLASSROOM: VIEWS FROM STUDENTS AND TEACHER - PRADIPTA, STEFANUS BINTANG; ARINI, RESTU (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT Technology in education has a very broad scope so that the use of technology in the teaching and learning process is very helpful and needed in today's era. With technology, students can build and increase their level of activeness in learning. However, in practice in the field, there are problems experienced by students in the classroom, namely the lack of involvement and activeness in class, where teachers must have appropriate methods or media to overcome this. This study aims to explore lived experiences of students and teacher at Universitas Mercu Buana Yogyakarta in using Padlet and Mentimeter as student response system in the Classroom. Four students and one teacher were selected based on their experience using Padlet and Mentimeter for more than two years. Through several questions asked with direct interviews. A qualitative approach with Purposive Sampling technique was employed to gain detailed insights into the experiences, benefits, barriers and features of Padlet and Mentimeter. This study reveals that Padlet and Mentimeter can make the learning experience more interesting, collaborative, and interactive. With both tool these two devices. students can provide direct feedback, participate in collaborative activities, and enjoy a dynamic classroom environment that encourages their participation. However, challenges such as adaptation time, reliance on internet connection, potential disruption of device use, and costs to access advanced features were identified. Despite those barriers, the combined use of Padlet and Mentimeter, offers educators the opportunity to create a more dynamic, interactive, and inclusive learning environment, ultimately increasing student engagement and participation in the learning process. ABSTRAK Teknologi dalam pendidikan memiliki cakupan yang sangat luas sehingga penggunaan teknologi dalam proses belajar mengajar sangat membantu dan dibutuhkan di era saat ini. Dengan teknologi, siswa dapat membangun dan meningkatkan tingkat keaktifannya dalam belajar. Namun dalam praktek di lapangan, terdapat permasalahan yang dialami oleh siswa di dalam kelas yaitu kurangnya keterlibatan dan keaktifan mereka di kelas, di mana guru harus memiliki metode atau media yang sesuai untuk mengatasi hal tersebut. Penelitian ini bertujuan untuk mengeksplorasi pengalaman hidup mahasiswa dan dosen di Universitas Mercu Buana Yogyakarta dalam menggunakan Padlet dan Mentimeter sebagai sistem respons mahasiswa di Kelas. Empat mahasiswa dan satu dosen dipilih berdasarkan pengalaman mereka menggunakan Padlet dan Mentimeter selama lebih dari dua tahun. Melalui beberapa pertanyaan yang diajukan dengan wawancara langsung. Pendekatan kualitatif dengan teknik Purposive Sampling digunakan untuk mendapatkan wawasan terperinci tentang pengalaman, manfaat, hambatan, dan fitur Padlet dan Mentimeter. Penelitian ini mengungkapkan bahwa Padlet dan Mentimeter dapat membuat pengalaman belajar lebih menarik, kolaboratif, dan interaktif. Dengan kedua alat ini, mahasiswa dapat memberikan umpan balik langsung, berpartisipasi dalam kegiatan kolaboratif, dan menikmati lingkungan kelas yang dinamis yang mendorong partisipasi mereka. Namun, tantangan seperti waktu adaptasi, ketergantungan pada koneksi internet, potensi gangguan penggunaan perangkat, dan biaya untuk mengakses fitur-fitur canggih telah diidentifikasi. Terlepas dari hambatan tersebut, penggunaan Padlet dan Mentimeter secara gabungan, menawarkan kesempatan kepada para pendidik untuk menciptakan lingkungan belajar yang lebih dinamis, interaktif, dan inklusif, yang pada akhirnya meningkatkan keterlibatan dan partisipasi mahasiswa dalam proses pembelajaran.